Caracterização do modelo de endofenótipo do transtorno bipolar do humor - Naraiana de Oliveira Tavares (2015)
Introduction: endophenotypes are sets of phenotypes which can be reached by biochemical, genetic, endocrine, inflammatory, neurophysiologic, anatomic, cognitive and personality measures, and thats what its nominated endophenotype model characterization. The models objective is to relate psychiatric disorders with the risk to develop the disease (risk factors). Objectives: bound the production networks social, scientific collaboration and researched themes which describe the bipolar disorders model. Verify the characteristics: sociodemographic, clinical, cognitive, personality, impulsiveness, and social skills in bipolar disorder patients, their first degree relatives, and a control group as possible indicators of the model. Method: qualitative study, with the use of social nets analysis methodology, and transversal study using a multidimensional evaluation which outcome is the identification of possible endophenotypes. The sample consisted of three groups with equal distribution of patients, families and controls. The data were treated with the descriptive and inferential statistics, identifying medial differences inter and intra groups. Was realized the univariate and marginal multivariate regression model to verify the correlation between the clinical, sociodemographic, personality and neuropsychological variables as mediation measures between the groups and it was generated a correlation coefficient between the groups. Finally, it was made a genotyping with the use of two markers tag rs4680 e rs4818 between the groups Results: the social net analysis identified the authors number who collaborated between themselves, the locations where the researches on endophenotypes are developed and the most recurrent thematic featuring the bipolar disorders endophenotype model. As for the comparison between the patients, non-affected relatives and control groups, identified a worst cognitive performance at the functions (attention, memory and executive function) and as for the personality: the group of bipolar disorder patients, their first degree relatives and the control group presented significant differences at the personality variables, which are the factors: novelties seeking (BN), (p < 0,001) and damage avoidance (ED), (p < 0,001). It was verified trough the groups performance, with patronized results (R), the following distribution: R(GTBH)< R(GTBHF)<R(GC). Only COMT SNP rs4818 for control group were in Hardy-Weinberg disequilibrium (2 =5,737; p=0,0166). In analysis, SNP rs4680 was associated to the presence of the G allele (p = 0.055) between the group of patients affected by bipolar disorder and the control group with estatítica significance (p <0.05). Conclusion: the results suggest that there are significant medial differences between the groups, as for the cognitive, personality, impulsiveness, social skills and genotype traces evaluations in some dimensions which characterize the bipolar disorders (BD) endophenotype model.